Vegetation type and climate determine temperature thresholds of soil respiration across drylands - María Almagro; Ana Rey; Rosa M. Inclán; Josep Barba; Rodrigo Vargas; Arnaud Carrara; José M. Grünzweig; Marcelo Sternberg; Yiftach Talmon; Rebecca L. McCulley; Sara Marañón-Jiménez; Penélope Serrano-Ortiz; et al. (Soil Biology and Biochemistry, 2025)

Diversity in Resource Use Strategies Promotes Productivity in Young Planted Tree Species Mixtures - Joel Jensen; Haben Blondeel; Joannès Guillemot; Florian Schnabel; Hernán Serrano‐León; Harald Auge; Lander Baeten; Nadia Barsoum; Jürgen Bauhus; Christel Baum; Raimundo Bermudez; Friderike Beyer; et al. (Global Change Biology, 2025)
Mixed‐species forestry is a promising approach to enhance productivity, increase carbon sequestration, and mitigate climate change. Diverse forests, composed of species with varying structures and functional trait profiles, may have higher functional and structural diversity, which are attributes relevant to a number of mechanisms that can influence productivity. However, it remains unclear whether the context‐dependent roles of functional identity, functional diversity, and structural diversity can lead to a generalized understanding of tree diversity effects on stand productivity. To address these gaps, we analyzed growth data from 83,600 trees from 89 species across 21 young tree diversity experiments spanning five continents and three biomes. Results revealed a positive saturating relationship between tree species richness and stand productivity, with reduced variability in growth rates among more diverse stands. Structural equation modeling demonstrated that functional diversity mediated the positive effects of species richness on productivity. We additionally report a negative relationship between structural diversity and productivity, which decreased with increasing species richness. When partitioning net diversity effects, we found that selection effects played a dominant role in driving the overall increase in productivity in these predominantly young stands, contributing 77% of the net diversity effect. Selection effects increased with diversity in wood density. Furthermore, acquisitive species with lower wood density and higher leaf nitrogen content had higher productivity in more diverse stands, while conservative species showed neutral to slightly negative responses to species mixing. Together, these results suggest that combining acquisitive with conservative species allows acquisitive species to drive positive selection effects while conservative species tolerate competition. Thus, contrasting resource‐use strategies can enhance productivity to optimize mixed‐species forestry, with potential for both ecological and economic benefits.

Multiyear Drought Strengthens Positive and Negative Functional Diversity Effects on Tree Growth Response - Hernán Serrano‐León; Haben Blondeel; Paula Glenz; Johannes Steurer; Florian Schnabel; Lander Baeten; Joannès Guillemot; Nicolas Martin‐StPaul; Georgios Skiadaresis; Michael Scherer‐Lorenzen; Damien Bonal; Matthieu Boone; et al. (Global Change Biology, 2025)
Mixed‐species forests are proposed to enhance tree resistance and resilience to drought. However, growing evidence shows that tree species richness does not consistently improve tree growth responses to drought. The underlying mechanisms remain uncertain, especially under unprecedented multiyear droughts. We used a network of planted tree diversity experiments to investigate how neighborhood tree diversity and species' functional traits influence individual tree responses to drought. We analyzed tree cores (948 trees across 16 species) from nine young experiments across Europe featuring tree species richness gradients (1–6 species), which experienced recent severe droughts. Radial growth response to drought was quantified as tree‐ring biomass increment using X‐ray computed tomography. We applied hydraulic trait‐based growth models to analyze single‐year drought responses across all sites and site‐specific responses during consecutive drought years. Growth responses to a single‐year drought were partially explained by the focal species' hydraulic safety margin (representing species' drought tolerance) and drought intensity, but were independent of neighborhood species richness. The effects of neighborhood functional diversity on growth responses shifted from positive to negative with increasing drought duration during a single growing season. Tree diversity effects on growth responses strengthened during consecutive drought years and were site‐specific with contrasting directions (both positive and negative). This indicates opposing diversity effects pathways under consecutive drought events, possibly resulting from competitive release or greater water consumption in diverse mixtures. We conclude that tree diversity effects on growth under single‐year droughts may differ considerably from responses to consecutive drought years. Our study highlights the need to consider trait‐based approaches (specifically, hydraulic traits) and neighborhood scale processes to understand the multifaceted responses of tree mixtures under prolonged drought stress. This experimental approach provides a robust framework to test biodiversity‐ecosystem functioning (BEF) relationships relevant for young, planted forests under increased drought stress.

Algorithms going wild – A review of machine learning techniques for terrestrial ecology - Cristina Cipriano; Sergio Noce; Simone Mereu; Monia Santini (Ecological Modelling, 2025)

Are trait responses of tree species across pyroregions indicative of fire-modulated plant functional strategies? - José Maria Costa-Saura; Gabriele Midolo; Carlo Ricotta; Mara Baudena; Carlo Calfapietra; Mario Elia; Paolo Fiorucci; Simone Mereu; Costantino Sirca; Donatella Spano; Gianna Vivaldo; Gianluigi Ottaviani (Perspectives in Plant Ecology, Evolution and Systematics, 2025)

Tree drought–mortality risk depends more on intrinsic species resistance than on stand species diversity - Renaud Decarsin; Joannès Guillemot; Guerric le Maire; Haben Blondeel; Céline Meredieu; Emma Achard; Damien Bonal; Hervé Cochard; Déborah Corso; Sylvain Delzon; Zoé Doucet; Arsène Druel; et al. (Global Change Biology, 2024)
Increasing tree diversity is considered a key management option to adapt forests to climate change. However, the effect of species diversity on a forest's ability to cope with extreme drought remains elusive. In this study, we assessed drought tolerance (xylem vulnerability to cavitation) and water stress (water potential), and combined them into a metric of drought–mortality risk (hydraulic safety margin) during extreme 2021 or 2022 summer droughts in five European tree diversity experiments encompassing different biomes. Overall, we found that drought–mortality risk was primarily driven by species identity (56.7% of the total variability), while tree diversity had a much lower effect (8% of the total variability). This result remained valid at the local scale (i.e within experiment) and across the studied European biomes. Tree diversity effect on drought–mortality risk was mediated by changes in water stress intensity, not by changes in xylem vulnerability to cavitation. Significant diversity effects were observed in all experiments, but those effects often varied from positive to negative across mixtures for a given species. Indeed, we found that the composition of the mixtures (i.e., the identities of the species mixed), but not the species richness of the mixture per se, is a driver of tree drought–mortality risk. This calls for a better understanding of the underlying mechanisms before tree diversity can be considered an operational adaption tool to extreme drought. Forest diversification should be considered jointly with management strategies focussed on favouring drought‐tolerant species.

Tree diversity enhances predation by birds but not by arthropods across climate gradients - Carla Vázquez‐González; Bastien Castagneyrol; Evalyne W. Muiruri; Luc Barbaro; Luis Abdala‐Roberts; Nadia Barsoum; Jochen Fründ; Carolyn Glynn; Hervé Jactel; William J. McShea; Simone Mereu; Kailen A. Mooney; et al. (Ecology Letters, 2024)
Tree diversity can promote both predator abundance and diversity. However, whether this translates into increased predation and top‐down control of herbivores across predator taxonomic groups and contrasting environmental conditions remains unresolved. We used a global network of tree diversity experiments ( TreeDivNet ) spread across three continents and three biomes to test the effects of tree species richness on predation across varying climatic conditions of temperature and precipitation. We recorded bird and arthropod predation attempts on plasticine caterpillars in monocultures and tree species mixtures. Both tree species richness and temperature increased predation by birds but not by arthropods. Furthermore, the effects of tree species richness on predation were consistent across the studied climatic gradient. Our findings provide evidence that tree diversity strengthens top‐down control of insect herbivores by birds, underscoring the need to implement conservation strategies that safeguard tree diversity to sustain ecosystem services provided by natural enemies in forests.

Enhancing Tree Performance Through Species Mixing: Review of a Quarter-Century of TreeDivNet Experiments Reveals Research Gaps and Practical Insights - Leen Depauw; Emiel De Lombaerde; Els Dhiedt; Haben Blondeel; Luis Abdala-Roberts; Harald Auge; Nadia Barsoum; Jürgen Bauhus; Chengjin Chu; Abebe Damtew; Nico Eisenhauer; Marina V. Fagundes; et al. (Current Forestry Reports, 2024)

Functional traits related to competition for light influence tree diameter increments in a biodiversity manipulation experiment - Raimondo Melis; Lourdes Morillas; Javier Roales; Jose M. Costa-Saura; Mauro Lo Cascio; Donatella Spano; Simone Mereu (European Journal of Forest Research, 2023)

Disentangling drivers of litter decomposition in a multi-continent network of tree diversity experiments - Ellen Desie; Juan Zuo; Kris Verheyen; Ika Djukic; Koenraad Van Meerbeek; Harald Auge; Nadia Barsoum; Christel Baum; Helge Bruelheide; Nico Eisenhauer; Heike Feldhaar; Olga Ferlian; et al. (Science of The Total Environment, 2023)

A height-wood-seed axis which is preserved across climatic regions explains tree dominance in European forest communities - José M. Costa-Saura; Antonio Trabucco; Donatella Spano; Simone Mereu (Plant Ecology, 2019)

Modeling ozone uptake by urban and peri-urban forest: a case study in the Metropolitan City of Rome - Lina Fusaro; Simone Mereu; Elisabetta Salvatori; Elena Agliari; Silvano Fares; Fausto Manes (Environmental Science and Pollution Research, 2018)

Contrasting effects of nitrogen addition on soil respiration in two Mediterranean ecosystems - Mauro Lo Cascio; Lourdes Morillas; Raúl Ochoa-Hueso; Silvana Munzi; Javier Roales; Niles J. Hasselquist; Esteban Manrique; Donatella Spano; Renée Abou Jaoudé; Simone Mereu (Environmental Science and Pollution Research, 2017)

A schizophrenia relevant 5-Choice Serial Reaction Time Task for mice assessing broad monitoring, distractibility and impulsivity - Huiping Huang; Simone Guadagna; Maddalena Mereu; Mariasole Ciampoli; Giacomo Pruzzo; Theresa Ballard; Francesco Papaleo (Psychopharmacology, 2017)

Contributions of a global network of tree diversity experiments to sustainable forest plantations - Kris Verheyen; Margot Vanhellemont; Harald Auge; Lander Baeten; Christopher Baraloto; Nadia Barsoum; Simon Bilodeau-Gauthier; Helge Bruelheide; Bastien Castagneyrol; Douglas Godbold; Josephine Haase; Andy Hector; et al. (Ambio, 2016)
The area of forest plantations is increasing worldwide helping to meet timber demand and protect natural forests. However, with global change, monospecific plantations are increasingly vulnerable to abiotic and biotic disturbances. As an adaption measure we need to move to plantations that are more diverse in genotypes, species, and structure, with a design underpinned by science. TreeDivNet, a global network of tree diversity experiments, responds to this need by assessing the advantages and disadvantages of mixed species plantations. The network currently consists of 18 experiments, distributed over 36 sites and five ecoregions. With plantations 1–15 years old, TreeDivNet can already provide relevant data for forest policy and management. In this paper, we highlight some early results on the carbon sequestration and pest resistance potential of more diverse plantations. Finally, suggestions are made for new, innovative experiments in understudied regions to complement the existing network.

Researches in Castelporziano test site: ecophysiological studies on Mediterranean vegetation in a changing environment - Lina Fusaro; Elisabetta Salvatori; Simone Mereu; Valerio Silli; Alessandra Bernardini; Aleandro Tinelli; Fausto Manes (Rendiconti Lincei. Scienze Fisiche e Naturali, 2015)

Tree-ring carbon and oxygen isotopes indicate different water use strategies in three Mediterranean shrubs at Capo Caccia (Sardinia, Italy) - Simona Altieri; Simone Mereu; Paolo Cherubini; Simona Castaldi; Carmina Sirignano; Carmine Lubritto; Giovanna Battipaglia (Trees, 2015)